Why networks matter in faith-related community development work: learning from diverse Christian responses to debt in England. (6th February 2019) - Orton, Andrew; Barclay, David
Abstract: This article explores the significant contribution being made by diverse Christian responses to debt in England, drawing on action research in London and the North East of England. These responses range from providing individual support and services to forms of organizing that tackle perceived causes through collective action and political campaigns. We show how complex links, relationships and networks have developed between responses, as those involved seek to generate more widespread, holistic and effective interventions. Through this, we show how these approaches have addressed related challenges by combining learning from different models and working across different scales, identities and boundaries, and consider wider learning for community development from this research.